“Awl is piercing me and society”: Webtoon as a Popular Adult Education Tool in South Korea - Jinhee Choi (Adult Education Research Conference, 2017)
The study illustrates the role of popular culture as an informal learning for both North and South Koreans to engage with unfamiliar, unpopular, and unvoiced themes in a public sphere.
Keywords: Informal Learning; North Korea; South Korea; Webtoon; Popular Culture